The Role of Case Managers in Hospitals: Scoping Review - Wahyu Fajar Rosaningtyas; Chriswardani Suryawati; Septo Pawelas Arso (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patient-centred care‘ refers to an approach to healthcare that is caring and responsive to patients’ preferences, needs and values, where patients are involved in discussions about their health condition. Experts have endorsed a case management-based nursing model to fulfil patients' preferences and rights to make care choices that meet their needs and expectations. One of the solutions developed to create more patient-centred care is the appointment of a case manager. This study aims to determine how case managers have implemented their role in hospitals in Indonesia and abroad. This study used a scoping review method. Articles were collected from online databases including ScienceDirect, PubMed, and Garuda with the keywords ‘role’ AND ‘case manager’ OR ‘nurse case manager’ OR ‘case management’ AND ‘hospitals’. Article selection was based on the PRISMA Extension for Scoping Review (PRISMA-ScR) guidelines. The results showed 11 articles that met the inclusion criteria. The results concluded the weaknesses and advantages of the case manager role. This study concluded that the roles of case managers both in Indonesia and abroad have similarities, but still have weaknesses and advantages of each.